Money in Islamic Economics Perspective - Aulia Putri, Mega; Trijunita Sari, Livia; Alia Rahma, Fuji (KnE Social Sciences, 2024)
In the very simple stages of human civilization, the provision of the necessities of life was carried out by exchanging necessities (bartering). Money has a very strategic position in the world economic system, so it is not easy to replace it with other media. In Islamic economics, money is only seen as a medium of exchange, and not as a commodity. The role of money is intended to eliminate injustice, dishonesty, and exploitation in the barter economy. Initially, the function of money was namely as a medium of exchange. However, in its development, the main function began to shift. Economic system analysts view the function of money not only as a medium of exchange but also as a commodity so that money can be bought and sold like a commodity. In this research, the author formulates a problem as to what is the concept of money from an Islamic economic perspective and its function from an Islamic economic perspective. In this research, the author uses library research methods. Keywords: money, economy, Islam